2015
DOI: 10.1021/acschembio.5b00430
|View full text |Cite
|
Sign up to set email alerts
|

Studying a Drug-like, RNA-Focused Small Molecule Library Identifies Compounds That Inhibit RNA Toxicity in Myotonic Dystrophy

Abstract: There are many RNA targets in the transcriptome to which small molecule chemical probes and lead therapeutics are desired. However, identifying compounds that bind and modulate RNA function in cellulo is difficult. Although rational design approaches have been developed, they are still in their infancies and leave many RNAs “undruggable”. In an effort to develop a small molecule library that is biased for binding RNA, we computationally identified “drug-like” compounds from screening collections that have favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…[7a, 8] In studies targeting r(CUG)-repeat sequences in 2015, Disney et al tested a drug-like, RNA-biased library of bis-benzimidazoles and similar core structures and found that bioactive molecules had statistically significant differences in topological polar surface area (tPSA) as well as hydrogen bond acceptors (HBA) and donors (HBD). [9] Inspired by this previous work and the recent surge in discoveries of biologically active RNA-targeting ligands, [10] we proposed to more broadly analyze the key guiding principles for specific RNA-targeting. In this work, we report the discovery of distinct physicochemical, structural, and spatial properties of RNA-targeted bioactive ligands, which are expected to facilitate the rapid discovery of RNA-targeted chemical probes and subsequent evaluation of the therapeutic potential of non-ribosomal RNAs.…”
mentioning
confidence: 99%
“…[7a, 8] In studies targeting r(CUG)-repeat sequences in 2015, Disney et al tested a drug-like, RNA-biased library of bis-benzimidazoles and similar core structures and found that bioactive molecules had statistically significant differences in topological polar surface area (tPSA) as well as hydrogen bond acceptors (HBA) and donors (HBD). [9] Inspired by this previous work and the recent surge in discoveries of biologically active RNA-targeting ligands, [10] we proposed to more broadly analyze the key guiding principles for specific RNA-targeting. In this work, we report the discovery of distinct physicochemical, structural, and spatial properties of RNA-targeted bioactive ligands, which are expected to facilitate the rapid discovery of RNA-targeted chemical probes and subsequent evaluation of the therapeutic potential of non-ribosomal RNAs.…”
mentioning
confidence: 99%
“…Some derivatives compete with aminoglycosides for binding to the bacterial rRNA A-site, others bind to the hepatitis C internal ribosomal entry site (IRES) and bis-benzimidazoles interact with CUG repeats that cause myotonic dystrophy type 1 [98]. Based on this knowledge a similarity search for small, druglike molecules containing the bis-benzimidazole or similar core structures was performed [99]. This resulted in a library of about 300 compounds with the potential to bind to RNA.…”
Section: Rna-focused Small Molecule Collection Based On Privileged Sumentioning
confidence: 99%
“…Moreover, the WST-1 assay requires less time than alternative approaches such as measurement of DNA synthesis by BrdU incorporation. WST-1 assays are widely used to perform screens for compounds that have an effect on cell viability [18-20]. …”
Section: Cell-based Assays To Assess Biological Activity Of Helicamentioning
confidence: 99%